Implementing AHP Method for Determining Level Priority of Vendor Selection - Kartika Salsabilla Wulandari; Sri Widaningrum; Sheila Amalia Salma (School of Industrial and System Engineering, Telkom University, 2023)
Vendors are suppliers of goods or services that help the production process of a company. One of the companies that carry out vendor selection is CV Milyarda Cipta Karya which is engaged in fashion. Vendor selection is an activity to determine vendors who will work with the company to help the production process. Based on an assessment of the 30 most popular CV Milyarda Cipta Karya's products on Shopee, there are consumer complaints about the inconsistent quality of materials. This problem is caused by the absence of standards governing the mechanism for selecting fabric vendors. Therefore, it is necessary to know the priority level of vendor selection criteria. Vendor selection criteria are Quality of goods, response time, location, flexibility, price, vendor inventory policy, and vendor service. The data needed in the design are vendor selection criteria according to William J Stevenson, namely hierarchical data and criteria weighting questionnaires. The method used to determine the priority level of vendor selection criteria is the Analytical Hierarchy Process method. Based on the calculation of the AHP method, the results obtained are the criteria for quality of goods 0.19, location 0.12, response time 0.12, vendor inventory policy 0.09, flexibility 0.09, price 0.11, and vendor service 0.28. The largest priority value is vendor service and the smallest is flexibility.